News aggregators influence on the quality of Internet-journalism - Chernetsky Petr Petrovich (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2015)
The article is devoted to the news aggregators and their impact on the quality of journalism in the Internet. The paper gives a definition of “news aggregators”, details the most famous of them, and lists some of the major problems which news aggregators are facing today. In addition, the article proves the thesis that news aggregators have a negative impact on the quality of news online. This is primarily due to the writing of the text for robots, not people, with a focus not on the quality and depth of the study, but the speed. Another major problem - the “theft” of news by websites-competitors and each other, as well as rewriting messages of various news services with a focus on sensationalism. All this leads to a general decline in the quality of journalistic texts on the Internet - in an effort to attract additional traffic news websites often the quality of materials are put into the background. At the end of the article it is made a forecast on the future of news aggregators.